RF Heating Due to a 3 T Birdcage, Whole-body Transmit Coil in Anesthetized Sheep - Turdumamatov, Samat; Oto, Cagdas; Algin, Oktay; Erguder, Hamza; Malas, Tahir (WILEY, 2020)
Purpose: To investigate the induced heating in vivo due to the radiofrequency (RF) power deposition from a 3 T birdcage, whole-body transmit coil. Method: Seven anesthetized and fleeced sheep were used in the study. The heating was induced by depositing the scanner-reported whole-body average specific absorption rate (SAR) between 1.6 and 4.0 W kg(-1) in sheep continuously for an hour. Two cases were studied, one, when the sheep head was placed in the isocenter (N = 3) and the other, when the sheep body was placed in the isocenter (N = 3). One sheep was used to evaluate the effect of anesthesia on the body temperature in the absence of any RF power deposition. The temperatures were measured using magnetic resonance (MR)-compatible fluoroptic probes. Results: The rate of brain temperature rise was measured as similar to 0.6-1.0 degrees C W-1 kg(-1) h(-1) when the sheep head was placed in the isocenter. In comparison, the rate of rectal temperature rise was measured as similar to 0.6-1.3 degrees C W-1 kg(-1) h(-1) when the sheep trunk was placed in the isocenter. Conclusions: The results suggest that the temperature change may exceed the maximum permissible safe temperature change limit in the body (i.e., 1 degrees C) with allowable RF power deposition.
Keywords: body coil; MRI; radiofrequency safety; 3 T; coil heating; TEMPERATURE; TISSUE; 9.4T; Spectroscopy